2019
DOI: 10.3390/su11051229
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Urban Public Transport Infrastructure and Social Equity and Spatial Accessibility within the Urban Environment: An Investigation of Tramlink in London

Abstract: The pursuit of sustainability has been at the forefront of contemporary planning initiatives. However, most recent research has focused on the environmental and economic aspects of developing sustainable urban environment, whilst largely neglecting the social aspects. Contemporary political thinking in the UK often disregards the potential of the urban infrastructure to improve social equity. The aim of this study was to analyse the impact of transport infrastructure on a variety of social measures, in an empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 59 publications
0
29
0
1
Order By: Relevance
“…Active accessibility variation increase (%) 19% SOCIAL SUSTAINABILITY: Accessibility to key services and facilities is defined as a primary measure of social sustainability [70]. Potentially, the urban infrastructure can improve social equity [71]. The revamping of the EUR will lead to reductions in users' travel time; therefore, it will increase accessibility and thus, the social equity by about 19% in the study area.…”
Section: 4mentioning
confidence: 99%
“…Active accessibility variation increase (%) 19% SOCIAL SUSTAINABILITY: Accessibility to key services and facilities is defined as a primary measure of social sustainability [70]. Potentially, the urban infrastructure can improve social equity [71]. The revamping of the EUR will lead to reductions in users' travel time; therefore, it will increase accessibility and thus, the social equity by about 19% in the study area.…”
Section: 4mentioning
confidence: 99%
“…There were 4,835 LSOAs in Greater London in 2011. The 2011 LSOA map is used as a basic boundary map in the analysis, which is in line with the previous study conducted in London by Cao and Hickman (2018) and Cuthill et al (2019). The resolutions of all data sets provided are at LSOA level.…”
Section: Notesmentioning
confidence: 92%
“…Building extensive public transport systems is now an objective for many cities internationally, with large amounts of funding being used for this purpose. Improving accessibility by public transport is usually the most efficient and only possible way to deliver large volumes of passengers to and from the larger metropolitan cities, and is important to improving access to activities (Cao and Hickman, 2019;Cuthill et al, 2019;Handy and Clifton, 2001;Pagliara and Papa, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Duran-Micco et al (2019) [59] compared several experiments on PT vehicles and proposed a memetic algorithm to minimize both total travel time and CO2 emissions. Cuthill et al (2019) [60] investigated a light-rail system in London using quantitative methods and indicated that the physical properties of PT infrastructure and the non-physical attributes of society could help individuals to succeed when combined. Ko et al (2019) [61] took environmental aspects into consideration and proposed a mathematical analysis of the environmental factors of forming a platoon of smart vehicles.…”
Section: Transportation Factormentioning
confidence: 99%